Scoring big: a bibliometric analysis of the intersection between sports and public relations - Hanny Hafiar; Heru Ryanto Budiana; Khairul Hafezad Abdullah; Davi Sofyan; Kholidil Amin (Cogent Social Sciences)
The escalating ubiquity of social media has intensified the influence of public relations on the general populace’s outlook toward sports and athletes. However, there are limited studies in the literature regarding an overview of public relations in the context of sports. This study addresses this gap by using bibliometric analysis to provide an overview of current trends and future developments in sports PR. The procedures have been executed by analysing the most productive authors and organisations, the frequently researched subjects, and the most cited publications. A comprehensive search of scientific databases was conducted to analyse 524 publications. The datasets retrieved in this study were analysed using ScientoPy and VOSviewer to identify tendencies and map the research themes based on the authors’ keywords. The findings highlight that the keywords frequently used by previous scholars are public relations, sports, and social media. An overall picture of the state of research on sport and public relations is given by this bibliometric analysis. The findings indicate that despite significant advancements in this domain, a considerable amount of work remains to be undertaken, particularly in underexplored areas such as sports communication and image restoration. The findings of this study can be advantageous for individuals involved in sports and public relations, including researchers, practitioners, and students.